The Religious, Cultural and Economic life of Tihama in The Islamic Heritage Books - Ali al-Shahrani, Saaid; Abdul Hamid, Faisal @ Ahamad Faisal; Ali @ Mat Zin, Aizan (Journal Al-Muqaddimah, 2018)
When we return to the sources of history and the Arab-Islamic heritage, we found that when talking about the Arabian island, the attention is paid to the big cities of Yemen and Hejaz, while the interest in the areas between Yemen and the Hijaz is almost nonexistent. In those regions, the area of Tihama is negligible, only in its relation to Yemen or Hijaz. This does not in any way mean that the region was poor in its production in all fields, whether it was religious, intellectual or economic aspects. As the region locates on the main road that links the northern and the southern Arabian Island, it has played an important role in intellectual and economic life. Based on this significance, I have studied this area in my research by using the descriptive, historical approach in writing and reviewing it through the religious, intellectual and economic aspects. It is worth mentioning that such a worthy subject of research and study. It needs to be concerted efforts to bring out a way out to fit the greatness of the area under study. Thus, the individual efforts remain deficient because of the difficulties faced the researcher from the lack of sources, and its validity to talk about Tihama. In addition, many of Manuscripts have not seen the light which belongs to the region (i.e. Tihama) . I revealed a finding in this study that through the Islamic heritage books, this region was full of poets and important commercial roads. Moreover, there were many idols than the delegations presented from Tihama to the Prophet peace be upon him declaring their Islam.